Triplet state properties of malonic acid C60 derivatives C60 [C(COOR)2] R = H, Et; n = 1-6 - Bensasson, René V.; Berberan-Santos, Mario; Brettreich, Michael; Frederiksen, J.; Gottinger, H.; Hirsch, Andreas; Land, E.; Leach, Sydney; McGarvey, David; Schönberger, Hubert; Schröder, C. (Physical Chemistry Chemical Physics, 2001)
Laser flash photolysis and pulse radiolysis have been used to determine properties of the lowest triplet state of a series of water-soluble malonic acid derivatives of C, C[C(COOH)] with n = 2-6, in water at pH 7.4. Similar studies were carried out on the corresponding ethyl esters, C[C(COOEt)] with n = 1-6, in the non-polar solvents, benzene or toluene. The properties include the T-T absorption spectra, the triplet molar absorption coefficients and the quantum yields of formation, Φ and Φ of the triplet and of singlet oxygen, respectively. This study shows a general tendency of the λ of the T-T absorption spectra, and of the Φ values to decrease with increasing number of addends. For regioisomers, the spectroscopic and photophysical parameters are modulated with the pattern of addition. The Φ quantum yields for the acids in aqueous solution are systematically lower than those of the ethyl esters in toluene. The lower Φ values observed for the acids in aqueous solution, and to a lesser extent for the esters in benzonitrile, can be interpreted as due to the presence of solute clusters in polar solvents.